Determining the factors affecting serum presepsin level and its diagnostic utility: A cross-sectional study. Issue 4 (April 2021) - Tsuchida, Tomoya; Ie, Kenya; Okuse, Chiaki; Hirose, Masanori; Nishisako, Hisashi; Torikai, Keito; Tanaka, Taku; Kunishima, Hiroyuki; Matsuda, Takahide
Abstract: Introduction: This study aimed to identify factors affecting presepsin levels and to determine their diagnostic utility. Methods: This cross-sectional study was conducted at an outpatient clinic and emergency department at an acute care hospital in Japan between January 2015 and December 2017. We enrolled 1, 840 consecutive outpatients with at least one measurement of serum presepsin, who were suspected of having bacterial infection. The outcome variables were bacterial infection, lower respiratory tract infection, urinary tract infection, cholangitis, and other infections diagnoses, based on the chart review. We collected blood analysis data on the patients' presepsin levels. Results: There was a significant association between presepsin level and the diagnosis of bacterial infection even when adjusted for age, sex, renal function, and biliary enzyme levels. An increase of 1 unit in the log of presepsin values resulted in a relative risk ratio of 1.71 (1.09–2.66), 2.1 (1.58–2.79), 2.93 (2.05–4.19), 4.7(2.90–7.61), and 2.41(1.70–3.43), for bacterial infection, lower respiratory tract infection, urinary tract infection, cholangitis, and other infections, respectively. Conclusions: Presepsin showed a statistically significant increase in the diagnosis of bacterial infections (lower respiratory tract infections, urinary tract infections, cholangitis, and non-severe patients) in a community hospital setting. However, in patients with renal dysfunction, presepsin levels should be interpreted with caution.